Rapid Bioassessment Protocols Using Aquatic Macroinvertebrates in Africa–Considerations for Regional Adaptation of Existing Biotic Indices - Dallas, Helen F. (Frontiers in Water, 2021)
Benthic macroinvertebrates form the basis of several biotic indices and are widely used globally to assess water quality and ecological condition of aquatic ecosystems. Many of these biotic indices are based on rapid bioassessment protocols (RBP). The first rapid bioassessment protocol (RBP) based on macroinvertebrates, developed in Africa in the early 1990s, was the South Africa Scoring System (SASS). Since then SASS has been widely used in southern Africa and beyond, and has formed the basis of several other RBPs developed in Africa. This paper explores the RBPs and associated biotic indices currently used in Africa, primarily those that are rapid, field-based with low taxonomy (mostly family level) and which rely on sensitivity weightings of individual taxa to generate three metrics for interpreting water quality and ecological condition of aquatic ecosystems. Recommendations for future regional adaptation of RBPs, including calibration, validation and modification of RBPs and biotic indices for new regions. To date, five RBPs have been developed in Africa, while some existing biotic indices have been used outside their intended regional range. Key to the efficacy of any RBP and associated biotic index is the ability to detect a water quality impact, or change in river health. Important considerations when adapting an index for a new region or country include evaluating the suitability of the sampling protocol to local river conditions, evaluating the distribution of aquatic macroinvertebrate taxa in the region, assigning sensitivity weightings to new taxa in the region, evaluating the ability of the biotic index to detect impacts, evaluating within-country spatial and temporal variability in macroinvertebrate assemblages, and developing appropriate data interpretation guidelines based on metric scores and reference conditions. Often several iterations of a biotic index are needed, with improvement in efficacy with each version, following spatially and temporally comprehensive sampling. Future RBPs developed for bioassessment of rivers in Africa will promote the protection, conservation and management of African riverine ecosystems.